1991
DOI: 10.1021/bi00106a018
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence study of a mutant cytochrome b5 with a single tryptophan in the membrane-binding domain

Abstract: Fluorescence studies of cytochrome b5 are complicated by the presence of three tryptophans, at positions 108, 109, and 112, in the membrane-binding domain. The cDNA for rabbit liver cytochrome b5, isolated from a lambda gt11 library, was used to generate a mutated mRNA where the codons for tryptophans-108 and -112 were replaced by codons for leucine. The sequence was expressed in Escherichia coli and the mutant protein was isolated. This mutant protein had the expected absorption spectrum, and its amino acid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 23 publications
(33 reference statements)
2
33
0
1
Order By: Relevance
“…To date, brominated phospholipids have been used to analyze binding of protein to vesicles [37,63], relative affinities of lipids to membrane proteins [64,65] and, through bromination at different positions in the alkyl chain, to investigate the topography of integral membrane proteins (e.g. [35,66]). Brominated detergents [36,38,43,67] appear to be a useful complement to brominated phospholipids to study membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…To date, brominated phospholipids have been used to analyze binding of protein to vesicles [37,63], relative affinities of lipids to membrane proteins [64,65] and, through bromination at different positions in the alkyl chain, to investigate the topography of integral membrane proteins (e.g. [35,66]). Brominated detergents [36,38,43,67] appear to be a useful complement to brominated phospholipids to study membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…REES is indeed observed when the above criteria are satisfied (Ladokhin et al, 1991;Mukherjee, 1993, 1999a,b;Chattopadhyay and Rukmini, 1993;Hutterer et al, 1996;Chattopadhyay et al, 1997;Ghosh et al, 1997;Santos et al, 1998;MacPhee et al, 1999;Raja et al, 1999;Granjon et al, 2001). In addition, it is preferable that the membrane-embedded molecule has only one fluorescent group which has a unique location in the membrane and not a distribution of locations.…”
Section: The Wavelength-selective Fluorescence Approachmentioning
confidence: 94%
“…In addition, the red edge effect has also been utilized to study the microconformational heterogeneity of the membrane-binding domain of cytochrome b 5 by comparing the information obtained from the native protein and its mutant which has a single tryptophan residue in this domain (Ladokhin et al, 1991). Both these proteins show a red shift in the emission spectrum when excited at the long wavelength edge of the excitation spectrum, indicating thereby that the tryptophan residue(s) in both cases are localized in a region of motional constraint.…”
Section: Application Of the Wavelength-selective Fluorescence Approacmentioning
confidence: 99%
“…The fluorescence probe TNS shows no such red edge excitation effect in methanol or dioxane (Lakowicz & Keating-Nakamoto, 1984) but shows REES when bound to proteins such as apomyoglobin, &lactoglobulin, &casein, the human a'-acid glycoprotein, and the serum albumins (Demchenko, 1982;Lakowicz & Keating-Nakamoto, 1984;Albani, 1992). REES of the tryptophan fluorescence of the intact eye lens (Rao et al, 1989), and of native and mutant cytochrome bs (Ladokhin et al, 1991), has also been recently reported.…”
mentioning
confidence: 99%